2010
DOI: 10.1021/ja1081487
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Ionomer-Electrified Metal Interface

Abstract: The competitive adsorption of Nafion functional groups induce complex potential dependencies (Stark tuning) of vibrational modes of CO adsorbed (CO(ads)) on the Pt of operating fuel cell electrodes. Operando infrared (IR) spectroscopy, polarization modulated IR spectroscopy (PM-IRRAS) of Pt-Nafion interfaces, and attenuated total reflectance IR spectroscopy of bulk Nafion were correlated by density functional theory (DFT) calculated spectra to elucidate Nafion functional group coadsorption responsible for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
155
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(168 citation statements)
references
References 29 publications
11
155
2
Order By: Relevance
“…This mode has been established to be dominated by motions of the Nafion exchange site in the sulfonic acid form that has no local symmetry (C 1 ). 22,[48][49][50] At potentials negative of 700 mV, Raman bands at 1066 cm −1 and 969 cm −1 emerge. These bands, also observed in the hydrated Nafion (red) IR spectrum, are the C 3V, HF and C 3V, LF group modes respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mode has been established to be dominated by motions of the Nafion exchange site in the sulfonic acid form that has no local symmetry (C 1 ). 22,[48][49][50] At potentials negative of 700 mV, Raman bands at 1066 cm −1 and 969 cm −1 emerge. These bands, also observed in the hydrated Nafion (red) IR spectrum, are the C 3V, HF and C 3V, LF group modes respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These group modes are consequent of a dissociated Nafion exchange site (sulfonate form) with C 3V local symmetry. 22,48,[51][52][53][54][55] C 1 normal mode eigenvector animation snapshots.-The dehydrated Nafion spectrum (blue) features bands at 1414 cm −1 and 910 cm −1 . These are group modes that have motional participation of the exchange group in the sulfonic acid form (C 1 local symmetry).…”
Section: Resultsmentioning
confidence: 99%
“…3N- 6 10 normal modes, for both repeat units, were used to assign IR bands. [29,31] The C 3V group modes (C 3V, 11 HF ; 1061 cm -1 and C 3V, LF ; 969 cm -1 ) arise from the same set of Nafion side-chain functional groups un-12 der fully hydrated conditions. The high frequency (HF) mode is dominated by a COC-A asymmetric 13 stretch.…”
Section: Manuscriptmentioning
confidence: 99%
“…This has been discussed previously. [31] The partial positive charge on the 8 sulfur decreases upon complexation with Li + and the partial negative charges on the oxygen atoms are 9 reduced due to the delocalization of charge to Li + . Clearly Li + symmetrizes the charge distribution 10 somewhat and lowers the overall dipole moment along the 3-fold axis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…He also found that the CF3CF3 groups are also strongly bound. [54] In this study we studied various adsorbed species on Pt, including water, oxygen, hydronium, and various Nafion fragments. From these simulations, we built a computational system to study the three-phase interface of a PEMFC.…”
Section: De-ee0000466 Ballard Materials Products Incmentioning
confidence: 99%